Open syntaxin overcomes exocytosis defects of diverse mutants in C. elegans - Chi-Wei Tien (Nature Portfolio, 2020)
Opening of the UNC-64/syntaxin closed conformation by UNC-13/Munc13 to form the neuronal SNARE complex is critical for neurotransmitter release. Here the authors show that facilitating the opening of syntaxin enhances exocytosis not only in unc-13 nulls as well as in diverse C. elegans mutants.